Mothers With Postpartum Psychiatric Disorders: Proposal for an Adapted Method to Assess Maternal Sensitivity in Interaction With the Child - Heinisch, Christine; Galeris, Mirijam-Griseldis; Gabler, Sandra; Simen, Susanne; Junge-Hoffmeister, Juliane; Fößel, Judith; Spangler, Gottfried (Frontiers in Psychiatry, 2019)
About 15 % of mothers suffer from postpartum psychiatric disorders such as depression, anxiety, or psychosis. Numerous studies have shown maternal caregiving behavior to be negatively affected under these circumstances. The current study sets out to shed light on specific caregiving behaviors of affected mothers in the context of parental mental illness at an early stage. There are several methods to assess maternal caregiving behavior in terms of sensitivity. However, all of them have limitations regarding the peculiarities of mothers with postpartum disorders, i.e. changes in affect regulation, and the early onset of the disorder postpartum. With the current study we provide an adapted method to assess maternal sensitivity based on methods recently approved in attachment research. Two groups of mothers, who were either healthy or had different postpartum disorders, were recorded on video during interactions with their infants. Behaviors were rated regarding responsiveness, promptness, appropriateness, intrusiveness, and positive and negative affect. A first analysis revealed an increased number of deficits on all subscales in mothers with postpartum psychiatric disorders as compared to healthy mothers. Depressive mothers with single-diagnosis had lower scores in responsiveness, promptness, and appropriateness, and higher scores on intrusiveness as compared to healthy mothers. Here, maternal behavior appears more parent-centered, while affect seemed to be relatively unharmed. Moreover, as compared to healthy mothers, mothers with comorbid depression and anxiety symptomatology achieved lower scores on responsiveness, appropriateness, and positive affect, and higher scores on intrusiveness and negative affect. It is suggested, that increased deficits are related to the severity of illness in mothers with comorbidities. Results on promptness indicate that these mothers are still capable of remaining higher vigilance to infant cues. Variance in maternal behavior was relatively high in clinical mothers showing that some of them are well capable of behaving in sensitive manner towards their child. One strengths of our adapted method is that particular aspects of sensitive parent–child interactions are assessed separately. This may shed light on specific behavior patterns of different postpartum psychiatric disorders, which may in turn relate to specific child outcomes. The manual is open for usage, while reliability testing is required.